2019
DOI: 10.1111/afe.12352
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the spider community in the olive grove agroecosystem (Portugal): potential bioindicators

Abstract: 1 Spiders are successful natural enemies in different crops. Research on the role of spiders as natural enemies within agroecosystems needs to address the distribution of their communities across different spatial scales, as well as the dominant species. 2 We studied the spatial distribution of the community of spiders of the olive agroecosystem in Northeastern Portugal and investigated potential species that could be used as bioindicators of agricultural management in the olive grove. 3 We found nine function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…These families are typically found in Mediterranean habitats, coinciding with olive‐growing areas. These results agree with those obtained in previous studies (Cárdenas et al, 2012; Dinis et al, 2016a; Picchi et al, 2016; Benhadi‐Marín et al, 2018, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These families are typically found in Mediterranean habitats, coinciding with olive‐growing areas. These results agree with those obtained in previous studies (Cárdenas et al, 2012; Dinis et al, 2016a; Picchi et al, 2016; Benhadi‐Marín et al, 2018, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The surrounding shrubland habitat represents an important type of land cover in the study area, corresponding to a typical Mediterranean habitat. The sampled areas are homogeneous and mainly characterized by an herbaceous stratum dominated by plants belonging to the families Asteraceae, Poaceae, and Fabaceae, a stratum of shrubs dominated by species such as Cistus ladanifer L., Cytisus spp., Lavandula spp., Rosmarinus officinalis L., Rubus ulmifolius Schott, and Crataegus monogyna Jacq., and an upper layer dominated by trees such as Quercus rotundifolia Lam., Quercus pyrenaica Willd., and Arbutus unedo L. (Benhadi‐Marín et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is wise to think that soil variables are more important drivers at local scales, and climate and spatial variables are more relevant when considering regional scales for soil arthropod species distribution. Spiders, carabids, and ants are successful natural enemies for pest control in agroecosystems (Eyre et al, 2016;Jacquot et al, 2017;Benhadi-Marín et al, 2020). They are sensitive agroecosystem bioindicators that have been used to monitor anthropogenic impact and agroecosystem health (Widhiono et al, 2017;Avgın et al, 2010;Borchard et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The structurally more complex vegetation of abandoned groves provided a wider range of microhabitats and especially more resources for feeding and refuge, which may have favored these groups. Several studies have shown that spiders are constrained by different habitat features at a local scale (e.g., [60,61]), favoring habitats with more complex vegetation architecture [62][63][64][65] and increased prey availability [66,67]. Therefore, the characteristics of the abandoned groves allowed them to sustain richer and more abundant spider communities.…”
Section: Discussionmentioning
confidence: 99%